Falling living standards during the COVID-19 crisis: Quantitative evidence from nine developing countries - Dennis Egger; Edward Miguel; Shana S. Warren; Ashish Shenoy; Elliott Collins; Dean Karlan; Doug Parkerson; A. Mushfiq Mobarak; Günther Fink; Christopher Udry; Michael Walker; Johannes Haushofer; et al. (Science Advances, 2021)
Despite numerous journalistic accounts, systematic quantitative evidence on economic conditions during the ongoing COVID-19 pandemic remains scarce for most low- and middle-income countries, partly due to limitations of official economic statistics in environments with large informal sectors and subsistence agriculture. We assemble evidence from over 30,000 respondents in 16 original household surveys from nine countries in Africa (Burkina Faso, Ghana, Kenya, Rwanda, Sierra Leone), Asia (Bangladesh, Nepal, Philippines), and Latin America (Colombia). We document declines in employment and income in all settings beginning March 2020. The share of households experiencing an income drop ranges from 8 to 87% (median, 68%). Household coping strategies and government assistance were insufficient to sustain precrisis living standards, resulting in widespread food insecurity and dire economic conditions even 3 months into the crisis. We discuss promising policy responses and speculate about the risk of persistent adverse effects, especially among children and other vulnerable groups.
Keywords: 300